ANALISIS PENGARUH KENAIKAN PAJAK TEMPAT HIBURAN TERHADAP MOTIVASI KERJA KARYAWAN - Sutrisno; Taryono (Universitas Nias Raya, 2025)
Employee motivation in the entertainment industry significantly influences productivity and service standards. Tax hikes in this sector can directly impact employees' well-being, reducing their motivation and performance. This research examines the effects of tax increases on employee motivation in the entertainment industry, focusing on concerns voiced by business owners such as Inul Daratista in her karaoke business. The study aims to identify effective strategies to maintain and enhance employee motivation to deliver high- quality services despite facing escalating tax challenges. Additionally, the research aims to provide policy recommendations that consider the welfare and motivation of employees in the entertainment sector. The research methodology employed is descriptive, aiming to depict individual characteristics and relationships among various phenomena in society. Secondary data from multiple relevant sources support the research analysis. A case study approach was chosen to delve into specific phenomena within real-world contexts, providing a comprehensive understanding of the impact of tax policies on the entertainment industry.